Chromosome numbers of some species of Pteris (Pteridaceae) in Java, Indonesia - TITIEN NGATINEM PRAPTOSUWIRYO; MUGI MUMPUNI (Biodiversitas Journal of Biological Diversity, 2018)
Praptosuwiryo TNg, Mumpuni M. 2018. Chromosome numbers of some species of Pteris (Pteridaceae) in Java, Indonesia. Biodiversitas 19: 2118-2126. Pteris L. (Pteridaceae) is a large fern genus consisting of about 250 species which distributed predominantly in tropical and subtropical countries. The genus grows in a diversity of ecosystems, either terrestrially or lithophytically, although most species occur in the forest. A study of the cytology of Pteris in Java is being undertaken for the conceptual understanding of the interrelationships between various fern species in the Malesian region. This aims of our study are: (1) to observe somatic chromosome number of some species of Pteris in Java; (2) to determine the reproduction types of the observed species by counting the spore number per sporangium; (3) to discuss polyploidy in the species in relation to plant morphological variation across their geographical distribution. Chromosome counts for eight species are reported. Pteris biaurita is an apogamous diploid species (2n = 58). Pteris ensiformis var. ensiformis has chromosome numbers of 2n = 87 (apogamous triploid) and 2n = 116 (sexual tetraploid), while                 P. ensiformis var. victoriae has a chromosome number 2n = 58 and is a sexual diploid. Pteris fauriei is an apogamous triploid species (2n = 87). Pteris longipinnula has a chromosome number of 2n = 116 (tetraploid). Pteris multifida and P. vittata are sexual tetraploids (2n=116). Pteris tripartita has two ploidy levels (sexual diploid and tetraploid). Another currently unplaced Javanese Pteris sp. has 2n = 87 (apogamous triploid). Diploid P. biaurita, tetraploid P. ensiformis, triploid P. fauriei, diploid P. tripartita, and teraploid P. vittata are new record cytotypes for Central Java. Polyploidy in the genus in relation to plant morphological variation across its geographical range is discussed.